Evaluasi dan Pengembangan Kebijakan Pendidikan di MAN 2 Deli Serdang - Muhammad Iqbal; Diva Pratama Rambe; Fitri Mushliha Simatupang; Mhd. Irgi Fahreza; Rizky Mutia Annisa (Jurnal Ilmiah Wahana Pendidikan, 2023)
The article entitled "Evaluation and Development of Education Policy at Man 2 Deli Serdang" focuses on the study of the formulation of educational policy evaluation and development. Education policy evaluation and development provides input to policy makers to take better steps. Evaluation is to find out the ability of students before attending lessons, as well as determining the field of study or major they will choose. Diagnostic evaluation, namely evaluation aimed at knowing and analyzing the condition of students, both with regard to the difficulties encountered, as well as the obstacles encountered in teaching and learning activities. evaluation of diagnosis, namely evaluation aimed at knowing and analyzing the condition of students, both with regard to the difficulties encountered, as well as the obstacles encountered in teaching and learning activities.